The representation of qurban in muslim designer community da’wah posters eid-al-adha theme - Ahmad Faiz Muntazori; Bambang Sunarto; Tommy Christomy (International Journal of Visual and Performing Arts, 2024)
Muslim Designer Community (MDC) is a forum for Muslim designers to actively conduct da’wah activities through visual media, especially in the form of posters. In this article, however, the theme that was chosen to be discussed is da’wah posters on Eid al-Adha. Eid al-Adha has an important value in Muslims because it concerns many things in Muslim life, both the vertical relationship between servants and their God, and the horizontal relationship between humans and humans and the social environment. This research focuses on the initial step in understanding MDC's da'wah posters, especially the posters related to Eid-Al-Adha as a multifaceted ritual in Islamic celebratory holy day, by dissecting the structure of da'wah posters posted by MDC through their social media account. This research uses a qualitative method. Data analysis was carried out using Roland Barthes' semiotics, namely by revealing visual markers as signifiers in da'wah posters. The result shows that the Eid al-Adha theme posters discussed above represent Qurban as the main message conveyed in the da'wah media using design elements in the form of artwork, visualizing the commands in the Qur'an and Hadith. Title and Image have a dominant role in conveying the message in the da'wah poster. The implication of this study shows that Da'wah posters are the implementation of religious values into the field of visual communication design, resulting in a new strategy of preaching using visual media. The combination of visual communication design and religious ideology has an important role in providing stimulus about religious messages to the audience.